2021
DOI: 10.1002/pol.20200866
|View full text |Cite
|
Sign up to set email alerts
|

ROP of L‐lactide and ε‐caprolactone catalyzed by tin(ii) and tin(iv) acetates–switching from COOH terminated linear chains to cycles

Abstract: The catalytic potential of tin(II)acetate, tin(IV)acetate, dibutyltin‐bis‐acetate and dioctyl tin‐bis‐acetate was compared based on polymerizations of L‐lactide conducted in bulk at 160 or 130°C. With SnAc2 low‐Lac/Cat ratios (15/1–50/1) were studied and linear chains having one acetate and one carboxyl end group almost free of cyclics were obtained. Higher monomer/catalyst ratios and lower temperatures favored formation of cycles that reached weight average molecular weights (Mw's) between 100,000 and 2,500,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The first critique of the JS theory was published by the first author in 2003 11 and 2014, 12 but did not suffice to rebut the widely accepted JS-theory. However, recently, the authors could demonstrate that reversible, like irreversible, polycondensations involve end-to-end (ete) cyclization, the existence of which was denied by J + S. 13,14 The existence of ete-cyclization has the consequence that all condensation products must be cycles regardless of the monomer structure and reaction conditions. Even more recently, the authors have found that reversible polycondensations exist, which proceed without the contribution of back-biting up to high conversions (98 ± 1%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first critique of the JS theory was published by the first author in 2003 11 and 2014, 12 but did not suffice to rebut the widely accepted JS-theory. However, recently, the authors could demonstrate that reversible, like irreversible, polycondensations involve end-to-end (ete) cyclization, the existence of which was denied by J + S. 13,14 The existence of ete-cyclization has the consequence that all condensation products must be cycles regardless of the monomer structure and reaction conditions. Even more recently, the authors have found that reversible polycondensations exist, which proceed without the contribution of back-biting up to high conversions (98 ± 1%).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental work presented by the authors was based on cyclic monomers and various tin catalysts. 13–15 However, the experimental work of Jacobson, Beckmann and Stockmayer (JBS) differs largely from that, because it is based on the polycondensations of 1,10-decanediol and adipic acid, and because toluene sulfonic acid (TSA) was used as the catalyst ((a) in Scheme 1). However, proton-catalyzed esterification and transesterification mechanisms (Scheme 1) and tin-carboxylate or phenoxide-catalyzed transesterification mechanisms (coordination–insertion mechanism) are quite different.…”
Section: Introductionmentioning
confidence: 99%
“…Kricheldorf and colleagues demonstrated that several tin catalysts could synthesize high molecular weight cyclic polymers within a short reaction time of less than 4 hours. 20–26 However, it should be noted that cyclic polymers obtained through REP typically exhibit a large polydisperse index compared to those obtained through LRC due to potential chain transfer reactions. 19…”
Section: Introductionmentioning
confidence: 99%
“…Until now, there have been limited studies on the physical properties such as molecular weight, intrinsic viscosity, and thermal properties 10,18–41 and hydrolytic degradation. 29,42 of cyclic polyesters.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of PEG-PLGA block copolymers via ROP, and more generally PLGA and polylactones, has been conducted thermally in the absence of catalysts 25,26 as well as using salt, 9,11,27,28 organometallic, 29 and organic catalysts. 23,30,31 While organocatalysts typically provide superior control over the polymerisation, generating polymers with expected molecular weights and narrow Đ values, 30,32 many display relatively high toxicities and may not be suitable for large or industrial scale production.…”
Section: Introductionmentioning
confidence: 99%